Modeling the Constant Composition Expansion Test of Black Oil Using Pressure, Volume, and Temperature (PVT) Calculations (Global Journals of Research in Engineering, 2024)
The black oil pressure volume and temperature PVT properties of well X were measured in the laboratory in a PT cell with subsurface and surface recombination samples Four sets of black oil samples were collected for the analysis The black oil standard test is a constant composition expansion test CCE separator flash test for volatile oils and rich oil gas condensate and a constant volume depletion test CVD The PVT analysis was carried out at Reservoir Fluid Laboratory Port Harcourt Oil samples were collected from the Q oil field The PVT analysis results were correlated to validate the bubble point pressure Pb oil isothermal combustibility Co oil formation volume factor Bo and the oil viscosity o The PVT report gives Po 2000 psi while the standing correlation gives Pb 1934 271 psi a difference of 65 7 psi i e 3 3 and solution gas oil ratio 647 3 SCF STB while the standing correlation gives 671 03 SCF STB a difference of 3 5 oil formation volume factor Bo of 1 456 res Bbl STB while standing correlations give Bo of 1 0675 res bbl STB a difference of 3 6 The isothermal compressibility of the oil ranges from 10 12 x 10-6 psi-1 at P Pb at 4500 psi to 4 1309 x 1018 cp at 15 psi The conclusion is that Gas began evolving at 2000 psig and increased as the pressure decreased Also it was noticed that at high pressure of 4500 psig the black oil viscosity was as low as 0 54 cp while at a lower pressure of 15 psiag the viscosity recorded was 1 38 cp The crude is of high viscosity with an average absolute error 3 5 0 035 The reservoir contains heavy crude oil with an API rating of 30
Keywords: isothermal pressure; volume; temperature; constant composition expansion; black oil